Using ‘systems awareness’: A proposed mechanism for monitoring communications - von Grebmer, Klaus; Hovland, Ingeborg (Bristol University Press, 2009)
Communication is an integral part of policy research, yet the impact of the communications process is difficult to monitor and evaluate. This paper reflects on one possible approach to monitoring communications, taking as its starting point ‘systems awareness’, or the awareness that communication efforts are situated within organisational, informational, social and political systems. Possible elements of a monitoring mechanism that takes these systems into account are proposed, and a brief example from the International Food Policy Research Institute (IFPRI) is included.